Новые виды тлей (Homoptera, Aphidinea) из Каневского биогеографического заповедника - Мамонтова, В.А. (Вестник зоологии, 1979)
Description and drawings are presented for five new species from the Kanev reservation (USSR): Chaitophorus flavissimus sp. n. from Salix caprea, Aphis coffeata sp. n. from Melampyrum nemorosum, Lypaphis berteroaella sp. n. from Berteroa incana, Semiaphis coryspermi Mam. (1964) from Coryspermum sp. and Myzus erytraeae sp. n. from Erythraeae centaurium.